2006
DOI: 10.1079/bjn20051568
|View full text |Cite
|
Sign up to set email alerts
|

Fat and protein metabolism in growing steers fed either grass silage or dried grass

Abstract: Cattle fed grass silage diets have been reported to have high carcass fat:protein ratios. The effect of grass silage and dried grass diets, fed at different levels of intake to ensure a range of equivalent metabolisable energy intakes (MEI) from 1 ·1 £ metabolisable energy requirement for maintenance to ad libitum, on fat and protein metabolism in twenty-four Hereford £ Friesian steers was investigated. After about 84 d of dietary treatment rates of whole-body fat and protein metabolism were measured, as were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…Similar daily NEG intakes were obtained by unsupplemented H1 and supplemented H2 bulls (65·1 and 64·0 MJ), and also by unsupplemented H2 and supplemented H3 bulls (57·4 and 57·2 MJ). In both cases, daily fat gains were similar, whereas daily lean gains were lower for bulls fed silage only, in line with Greathead et al. (2006), who found that high carcass fat:protein ratios of cattle offered grass silage diets compared with dried grass, at equal ME intakes, were due to limited rates of protein accretion rather than excess carcass fat accretion.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Similar daily NEG intakes were obtained by unsupplemented H1 and supplemented H2 bulls (65·1 and 64·0 MJ), and also by unsupplemented H2 and supplemented H3 bulls (57·4 and 57·2 MJ). In both cases, daily fat gains were similar, whereas daily lean gains were lower for bulls fed silage only, in line with Greathead et al. (2006), who found that high carcass fat:protein ratios of cattle offered grass silage diets compared with dried grass, at equal ME intakes, were due to limited rates of protein accretion rather than excess carcass fat accretion.…”
Section: Discussionsupporting
confidence: 82%
“…, 1995), it cannot be excluded that the total supply of AAT, or the supply of some single amino acids, e.g. leucine (Greathead et al. , 2006), may have been at suboptimal levels in diets based on silage only, especially to support the high growth rate (1423 g d −1 ) of unsupplemented H1 bulls.…”
Section: Discussionmentioning
confidence: 99%
“…Growing cattle fed grass silage had a lower lean-to-fat ratio than those fed an isoenergetic dried grass diet, as a result of a limited rate of protein accretion without variations in fat accretion (Greathead et al, 2006). Simultaneously, grass silage tended to increase the weight of internal WAT and increased lipogenic activities in perirenal AT.…”
Section: Nutritional and Physiological Control Of Muscular And At Growthmentioning
confidence: 94%
“…We speculate that feeding with larger amounts of concentrate diets changes rumen bacterial flora to produce more amounts of propionate followed by stimulating insulin secretion in beef cattle and more amounts of insulin may accelerate fatty acid synthesis in tissues including skeletal and influence marbling conditions in beef cattle with high TDN. Indeed, the role of insulin in directing fat metabolism in ruminants is uncertain (Greathead et al., 2006); for example, Smith et al. (1992) were unable to demonstrate a correlation between insulin and fatty acid synthesis in vitro , whereas Mills et al.…”
Section: Discussionmentioning
confidence: 99%